ผลการดื่มน้ำ น้ำเกลือ และน้ำตาล ต่อความสามารถในการทำงานของร่างกาย - เผด็จ นวนหนู (จุฬาลงกรณ์มหาวิทยาลัย, 1978)
The purpose of this study was to investigate the effects of water, salt, and sugar replacement on physical performance. Twenty-five healthy male freshmen students from Srinakharinvirot Palasuksa University volunteered to be subjects. These subjects were then selected to only twelve of them who were in similar physical fitness level. The similarity of their physical fitness were based on the results of physical working capacity 170 (PWC170) testing. Prior to the experiment, subjects pedaled on the Monark bicycle ergometer at a speed of 50 revolutions per minute for 1 hour. The testing room temperature was kept constantly at 26-28 C with 70± 5% humidity. The work load was at 70% of maximum work from the first PWC170 test. The subjects were permitted to rest for 30 minutes before the next test. Four testing conditions were given to each subject with a two-day interval : namely (1) normal body condition, (2) water replacement, (3) salt replacement, and (4) sugar replacement. The exercise work load started at the pre-determined intensity. It was increased 25 watts for every 2 minutes till the working heart rate reached 180 beats/minute or exhaustion. Results revealed that the physical working capacity determined from the maximum quantity of work done after water, salt, and sugar replacement were not significantly different among groups at the 0.1 level. However, if determined from the total quantity of work done, results showed that physical working capacity at normal condition, water, salt, and sugar replacement were not significantly different. All these tests yielded better physiological response than that of the normal condition. It was concluded that in a profound endurance exercise, water, salt, and/or sugar replacement would improve working efficiency.